2014
DOI: 10.1371/journal.ppat.1004236
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Imaging Reveals the Dynamics of Leukocyte Behaviour during Experimental Cerebral Malaria Pathogenesis

Abstract: During experimental cerebral malaria (ECM) mice develop a lethal neuropathological syndrome associated with microcirculatory dysfunction and intravascular leukocyte sequestration. The precise spatio-temporal context in which the intravascular immune response unfolds is incompletely understood. We developed a 2-photon intravital microscopy (2P-IVM)-based brain-imaging model to monitor the real-time behaviour of leukocytes directly within the brain vasculature during ECM. Ly6Chi monocytes, but not neutrophils, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
103
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(112 citation statements)
references
References 72 publications
8
103
1
Order By: Relevance
“…(35)(36)(37)(38)(39). Moreover, recent studies revealed a role for inflammatory monocytes, in the recruitment of CD8 + T cells to the brain of P. berghei ANKA-infected mice (40).…”
Section: Discussionmentioning
confidence: 99%
“…(35)(36)(37)(38)(39). Moreover, recent studies revealed a role for inflammatory monocytes, in the recruitment of CD8 + T cells to the brain of P. berghei ANKA-infected mice (40).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect was modest (ϳ2-to 3-fold) for all parameters. Decreases in T cell recruitment of similar magnitude, resulting from depletion of inflammatory monocytes, do not result in protection from ECM (58). Therefore, it seems unlikely that the observed diminution in the absolute number of recruited CD8 ϩ T cells could account for the dramatically divergent clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…PbA-infected Irgm3 Ϫ/Ϫ mice had reduced CCL2 protein as well as decreased monocyte sequestration in the brain. The presence of monocytes is obvious in ECM brain lesions, and they have been shown to enhance recruitment of CD8 ϩ T cells to the brain during ECM, probably via production of T cell-attracting chemokines (58). However, inflammatory monocytes are nonessential for the development of ECM pathogenesis (58,59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some conditions or diseases, for example, multiple sclerosis, most leukocytes transmigrate through the endothelial barrier and infiltrate into the adjacent tissues, causing lesions in the affected area (Compston and Coles, 2008). On the contrary, as in cerebral malaria, a few leukocytes transmigrate through the endothelium, but most are sequestrated within the microvessels, thus inducing local ischemia (Coltel et al, 2004;Pai et al, 2014). Yet, the reasons leading to leukocyte transmigration or sequestration in different conditions are poorly understood.…”
Section: Introductionmentioning
confidence: 99%